Noble metal (Pd, Ru, Rh, Pt, Au, Ag) doped graphene hybrids for electrocatalysis - Giovanni, Marcella (2013)
Metal decorated graphene materials are highly important for catalysis. In this work, noble metal doped-graphene hybrids were prepared by a simple and scalable method. The thermal reductions of metal doped-graphite oxide precursors were carried out in nitrogen and hydrogen atmospheres and the effects of these atmospheres as well as the metal components on the characteristics and catalytic capabilities of the hybrid materials were studied. The hybrids exfoliated in nitrogen atmosphere contained a higher amount of oxygen-containing groups and lower density of defects on their surfaces than hybrids exfoliated in hydrogen atmosphere. The metals significantly affected the electrochemical behavior and catalysis of compounds that are important in energy production and storage and in electrochemical sensing. Research in the field of energy storage and production, electrochemical sensing and biosensing as well as biomedical devices can take advantage of the properties and catalytic capabilities of the metal doped graphene hybrids.